Blood Transfusion Frequency and Indications in Yemeni Children with Sickle Cell Disease - Abdul-Wahab M. Al-Saqladi; Dikra M. Maddi; Aida H. Al-Sadeeq (Anemia)
Background. Blood transfusion is an essential component in the care of patients with sickle cell disease (SCD), but it might be associated with serious acute and delayed complications. This study was aimed to describe red cell transfusion patterns and indications among hospitalized SCD children in a low-resource setting. Patients and Methods. A retrospective, descriptive study of all children (≤16 years) with SCD who received blood transfusion therapy during their hospital admissions in the pediatric department at Al-Sadaqa Teaching Hospital in Aden, Yemen, for a period of one year. Results. Out of 217 hospitalized children with SCD, 169 (77.9%) were transfused and received 275 RBC transfusion episodes. The mean age of transfused children was 6.9 ± 4.6 years and 103 (60.9%) were males, with a male/female ratio of 1.6 : 1 (p=0.004). Hemoglobin (Hb) levels were significantly lower in the transfused than in the nontransfused (Hb 5.5 ± 1.5 vs. 7.7 ± 1.5 g/dL, p=0.03). Pretransfusion Hb levels were ˂7.0 g/dL in 86.2% and ˂5.0 g/dL in 39.3% of patients. Single transfusion was given to 122 (72.2%) and 5 or more transfusions in 9 (4.15%) of patients on different occasions. Simple (top-up) transfusion was used in all transfusion events. Commonest indications for transfusion were anemic crises (41.1%), vasoocclusive crises (VOC) (13.8%), VOC with anemic event (11.3%), acute chest syndrome (8.7%), and stroke (7.3%). Conclusion. Intermittent blood transfusion remains a common practice for the management of children with acute SCD complications. Main indications were acute anemic crises, severe pain crises, ACS, and stroke. In limited resource settings, such as Yemen, conservative transfusion policy appears to be appropriate.